A histochemical comparison of methyl green-pyronin, and hematoxylin and eosin for detecting apoptotic cells in oral squamous cell carcinoma, oral leukoplakia, oral submucous fibrosis and normal oral mucosa. (May 2015) - Sumedha, S; Kotrashetti, VS; Somannavar, P; Nayak, R; Babji, D
Abstract Analysis of apoptotic cells in oral pathological states could be useful for determining the rates of tissue turnover, which would help determine prognosis. The use of histochemical stains such as hematoxylin and eosin (H & E) and methyl green-pyronin (MGP) can provide a simple and cost-effective method for detecting apoptotic cells. We compared the efficacy of MGP and H & E for detecting apoptotic cells in oral squamous cell carcinoma (OSCC), oral leukoplakia (OL), oral submucous fibrosis (OSMF) and normal oral mucosa (NOM). Ten cases each of OSCC, OSMF, OL and NOM were retrieved from the archives and two serial sections were stained, one with H & E and the other with MGP. Apoptotic cells were identified at 100 x magnification and the apoptotic index was calculated. Apoptotic cells were distinguished more readily in MGP stained sections than in those stained with H & E. Also, the apoptotic cell count was greater in OSCC compared to OL, OSMF and NOM. We concluded that MGP staining can be used as a routine, cost-effective method for detecting apoptotic cells.